Peroral Pharyngeal Block for Placement of Esophageal Endoprostheses. Issue 2 (March 1992) - Valley, Marc A.; Kalloo, Anthony N.; Curry, Craig S.
Abstract : Background and Objectives: The placement of plastic peroral endoprostheses frequently is done in the United States as a palliation for esophageal cancer. However, the combination of topical local anesthetics and sedatives, the most commonly used means to achieve anesthesia, can cause complications and often does not adequately suppress the gag reflex. The purpose of this study was to compare sedation requirements in patients receiving the standard topical local anesthetic versus patients receiving peroral pharyngeal plexus block. Methods: From December 1987 through April 1991, 11 patients underwent endoscopic esophageal stent placement. The first six patients received topical 10% lidocaine spray, the other five patients received pharyngeal plexus blocks. Supplemental sedation was given until the patient closed their eyes but were responsive to verbal stimuli. Completeness of block was evaluated by stimulating the posterior oropharynx. Total sedative requirements were recorded for each patient. Results: Patients receiving pharyngeal plexus block had profound anesthesia and suppression of the gag reflex, as determined by examination and the patient's tolerance of the procedure. Patients receiving only topical anesthesia and intravenous sedation tolerated the procedure poorly and required a greater amount of intravenous sedation than those in the blocked group ( p < 0.01). There were no anesthetic complications in patients receiving pharyngeal blocks. Conclusions: Our experience indicates that the endoscopic placement of esophageal endoprostheses is optimally performed with the aid of pharyngeal plexus block. This block provides profound anesthesia with minimal risk in debilitated, high-risk patients. The neuroanatomy of the oropharynx is also reviewed.